The Internal Distribution of Union Rents: An Empirical Test of the Voting Power Model - Parsons, Donald O. (The Review of Economics and Statistics, 1992)
The egalitarian wage policies of labor unions in the United States have been attributed to low-skilled majorities pursuing their self-interest in a majority rule environment. For this hypothesis to be more than a formalization of stylized facts requires evidence that unions are not egalitarian when the work place is not characterized.by a low-skilled majority. The author considers the impact of high-skilled majorities on (1) voting behavior in certification elections and (2) rent distribution policies in existing unions. Neither analysis supports the belief that union rent distribution policies are driven by skill-group coalitions pursuing their self-interests. Copyright 1992 by MIT Press.